2022
DOI: 10.1021/acs.orglett.2c03382
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Silicon-Substituted Hemicyanines for Multimodal SWIR Imaging

Abstract: SWIR dyes offer many advantages over their more common NIR congeners; however, the available options are limited. New SWIR imaging agents can be accessed by remodeling existing NIR molecules (i.e., hemicyanines (HDs)). In this study, we synthesized SWIR-HD, a modified HD featuring dimethylsilicon and benzo[cd]indolium groups that are designed to red-shift the absorbance and emission to 988 and 1126 nm, respectively. SWIR-HD was employed to visualize the liver and tumors via multimodal SWIR imaging.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…As another example, HDs are a series of popular hemicyanine dyes which emit in the NIR-I region; 52,53 Chan and co-workers found that, by replacing the oxygen atom of HD dyes in the terminal donor part with the SiMe 2 group, the emission wavelength of Si-HDs would redshift about 350 nm to the NIR-II region. 54 Since the 1930s, researchers have observed the phenomenon of J-aggregation with a narrow absorption band turning to a longer wavelength compared with the monomer absorption band and a nearly resonant fluorescence (tiny Stokes shift) with a narrow band. 55 For many J-aggregates, bathochromic shifts beyond 100 nm are observed, attributed to excited states formed by extended domains of coherently coupled molecular transition dipoles.…”
Section: Wavelength Extension Principles Of Polymethine Fluorophoresmentioning
confidence: 99%
See 1 more Smart Citation
“…As another example, HDs are a series of popular hemicyanine dyes which emit in the NIR-I region; 52,53 Chan and co-workers found that, by replacing the oxygen atom of HD dyes in the terminal donor part with the SiMe 2 group, the emission wavelength of Si-HDs would redshift about 350 nm to the NIR-II region. 54 Since the 1930s, researchers have observed the phenomenon of J-aggregation with a narrow absorption band turning to a longer wavelength compared with the monomer absorption band and a nearly resonant fluorescence (tiny Stokes shift) with a narrow band. 55 For many J-aggregates, bathochromic shifts beyond 100 nm are observed, attributed to excited states formed by extended domains of coherently coupled molecular transition dipoles.…”
Section: Wavelength Extension Principles Of Polymethine Fluorophoresmentioning
confidence: 99%
“…For instance, the oxygen atoms of the symmetric polymethine fluorophore IR-971 was substituted by sulfur atom, resulting in an approximately 90 nm bathochromic shift. As another example, HDs are a series of popular hemicyanine dyes which emit in the NIR-I region; , Chan and co-workers found that, by replacing the oxygen atom of HD dyes in the terminal donor part with the SiMe 2 group, the emission wavelength of Si-HDs would redshift about 350 nm to the NIR-II region …”
Section: Design Principles Of Polymethine Fluorophoresmentioning
confidence: 99%
“…For example, Chan’s group shifted the wavelengths of hemicyanine fluorophores by heteroatom substitution strategies, which can be used to visualize liver and tumors through multimodal shortwave infrared (SWIR, 900–1700 nm) imaging. 38 Furthermore, Miao’s group constructed several NIR-II fluorophores by modifying the donor–π–acceptor for visualizing amyloid-β in vivo (Figure 12 ). 39…”
Section: Construction Of Hemicyanine Fluorophores In the Nir-ii Regionmentioning
confidence: 99%
“…A wide range of biomarkers ranging from the production of ROS to increased activity of certain liver enzymes has been associated with liver damage. By taking advantage of these changes, the diversity of activatable probes suitable for molecular imaging of the liver has greatly expanded. …”
Section: Liver Imagingmentioning
confidence: 99%